PENDEKATAN BIG DATA ANALYTICS UNTUK OPTIMASI KINERJA SISTEM INFORMASI - Pangestu, Aji Dewo; Harahap, Lailan Sofinah (LPPM Universitas Bina Bangsa, 2024)
The digital age has had a significant impact through advancements in sensor technology, internet connectivity, and growing storage capacity, giving rise to the phenomenon of Big Data. In this landscape of abundant information, data processing and analysis become challenges that require effective solutions. This article explains the importance of Big Data Analytics in the context of Information Systems, where the presence of Big Data is not only a necessity but also an opportunity to gain deep insights from the ever-growing data. Proper data processing is crucial to uncovering the value of Big Data, involving comprehensive data analysis and machine learning training. The integration of sensor technology, internet connectivity, advanced storage, and intelligent data processing forms the basis for advancements in the Big Data Analytics domain. This research aims to explore the utilization of Big Data Analytics in improving the performance of Information Systems. Through a conceptual foundation and literature review, this article presents the theoretical basis that supports the research. The practical implementation of Big Data Analytics is described to illustrate how this technology can be realistically applied to optimize Information Systems. The research method uses Systematic Literature Review (SLR) to identify, evaluate, and interpret related research. An in-depth literature review, secondary data collection and analysis, and examination of ideas and models related to governance and corporate strategy were the focus of the research. The results and discussion highlight the critical role of Big Data Analytics and information systems in the Big Data era, emphasizing effective integration as the key to optimizing results. This article is expected to contribute to the development of an increasingly dynamic information,paradigm.